A new species of lizard endemic to sierra de fiambalá, northwestern argentina (Iguania: Liolaemidae: Phymaturus). integrated taxonomy using morphology and DNA sequences: Reporting variation within the antofagastensis lineage - Lobo Gaviola, Fernando Jose (2019)
The northernmost distributed group of lizards belonging to Phymaturus occurs in rocky outcrops of the Puna region between 3600-4200 m in Argentina. In a recent phylogenetic study based on morphological and genetic information, the monophyly of this small lineage was corroborated. This group is formed by Phymaturus antofagastensis, P. laurenti, P. denotatus, P. mallimaccii and a population of uncertain taxonomic status until the present study. After obtaining new samples and observations, we described a new species belonging to this lineage that is known only from Sierra de Fiambalá, being the species of Phymaturus living at the highest elevation ever recorded (4500 m). Males have a homogeneous yellow dorsum and lack melanic coloration over their heads, a phenomenon found in males of most species of the palluma group. We provide a detailed diagnosis, including characters from the squamation, coloration and significant differences found among continuous characters (ANOVA). Furthermore, we present genetic distances among members of the mallimaccii subclade based on sequences of the cytb marker. We provide color photos showing pattern variation of males and females. We reanalyze the phylogenetic relationships within the entire palluma group and update info on all members of the antofagastensis lineage based on new samples and make a better supported hypothesis. We also evaluate the phylogenetic position of the new taxon.